How the mapping of threshold concepts across a master’s programme in health professions education could support the development of mastersness - Archer, E.; Schmutz, A. M. S.; Volschenk, M.; Jacobs, C. (BMC medical education, 2024)
Introduction Global trends towards the professionalization of Health Professions Education (HPE) have catalyzed the proliferation of degree-awarding programmes in HPE. We apply the theoretical lens of threshold concepts to explore the required levels of Master’s in HPE (MHPE) learning and teaching, with a view to determining how students might be supported to engage meaningfully with learning. Methods Qualitative data were collected with a series of nominal group discussions. The methodology and data analysis followed a consensus building approach. Results Four threshold concepts were identified: Being in the HPE world, the nature of HPE knowledge, the nature of HPE practice and the nature of HPE scholarship. We also mapped the threshold concepts to the World Federation for Medical Education (WFME) master’s level academic skills and the Scottish Quality Assurance Agency (QAA) facets of mastersness. Conclusion It is envisaged that our findings will enhance alignment between the outcomes and assessment in an MHPE programme, form the basis of understanding feedback received from students, and inform teaching and supervisory practices. The findings also complement the WFME and QAA frameworks by clarifying the depth and complexity of academic skills expected at master’s level and informing teaching and learning approaches to support the development of the identified threshold concepts.